The construction of the Satire poem of the poet Jarir - Sharara, Murtadha Ali (Journal of Humanities & Social Sciences, 2021)
This research deals with the construction of the orthographic poem of the Umayyad poet Jarir bin Attia, who was famous for what is called the poetry of the opposites (alnaqayid), with two of the most famous Umayyad poets, Al Farazdaq and Al Akhtal. The research discusses the topic through three sections, the first deals with the motivations for satire in Jarir, psychologically, socially and artistically, and the second section is a theoretical description of Jarir’s method of constructing his satirical poem to achieve victory, primarily objectively, and the research deals with the technical aspects in furtherance of the main ones. As for the third section, it included an application to an alphabetical Jerry text, in which the poet Jarir spells his archenemy, the logical and conquering opponent, using his alphabetical ingenuity with all intelligence and ability, which shows that spelling is an integrated creative project by Jarir and not just an emotional reaction. The twelve with the Akhtal. Then the research concludes with a conclusion that includes the results.